Popular terminology for "abduction"of girls - Rajković, Marijeta (2007)
During the 1960-ies, ethnographic material was collected on the territory of former Yugoslavia for the Ethnological Atlas. A theme number 119, presented in this research was entitled Irregular ways of getting married. More precisely, there were three different types of "abduction" ; a real one (against the will of both a girl and her family), arranged abduction a) with the girl's permission, b) with the girl's permission, but without the permission of her family, and finally c) fake abduction - with the permission of both, the girl and the family, but with a violent pretence. A presentation of popular terminology of abduction obtained from 3200 questionnaires of the Ethnological Atlas of Yugoslavia, covering the whole territory of former Yugoslavia is shown in this article.
Projekt MZOS
ENG